Treatment of Anorectal Malformations in German Hospitals: Analysis of National Hospital Discharge Data from 2016 to 2021 - Wilms, Miriam; Jenetzky, Ekkehart; Märzheuser, Stefanie; Busse, Reinhard; Nimptsch, Ulrike (European Journal of Pediatric Surgery, 2024)
Background Anorectal malformations (ARMs) are complex congenital anomalies. The corrective operation is demanding and schedulable. Based on complete national data, patterns of care have not been analyzed in Germany yet.Methods All cases with ARM were analyzed (1) at the time of birth and (2) during the hospital stay for the corrective operation, based on the national hospital discharge data (DRG statistics). Patient's comorbidities, treatment characteristics, hospital structures, and the outcome of corrective operations were analyzed with respect to the hospitals' caseload.Results From 2016 to 2021, 1,726 newborns with ARM were treated at the time of birth in 388 hospitals. Of these hospitals, 19% had neither a pediatric nor a pediatric surgical department. At least one additional congenital anomaly was present in 49% of cases and 7% of the newborns had a birthweight below 1,500 g.In all, 2,060 corrective operations for ARM were performed in 113 hospitals in the same time period. In 24.5% of cases, at least one major complication was documented. One-third of the operations were performed in 56 hospitals, one-third in 20 hospitals, and one-third in 10 hospitals with median annual case numbers of 2, 5, and 10, respectively.Hospitals with the highest caseload operated cloacal defects more often than hospitals with the lowest caseload (7 vs. 2%) and had more early complications than hospitals with the lowest caseload (30 vs. 21%). This difference was not statistically significant after risk adjustment.Conclusions Children with ARM are multimorbid. Early complications after corrective surgery are common. Considering the large number of hospitals with a very low caseload, centralization of care for the complex and elective corrective surgery for ARM remains a key issue for quality of care.
Keywords: anorectal malformation; volume–outcome relationship; quality of care